Tinjauan Hukum Islam terhadap Operasi Selaput Dara dan Keharmonisan Keluarga - Sofyan, Aa (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
This study aims to analyze the status of Islamic law in hymen surgery which is becoming a trend among the public, so that legal certainty will be known whether it is permissible or prohibited to do, so that it becomes a reference for people who will carry out hymen surgery. The method used in this study is a qualitative method using a document approach. The document study approach is a study that focuses on the analysis of written materials based on their context, materials can be in the form of books, scientific publications, newspapers, manuscripts, or articles. In this study, it can be concluded that most of the teenage girls who have lost their virginity are caused by promiscuity as evidenced by the results of a survey conducted by the Indonesian Child Protection Commission, many of them even become pregnant out of wedlock as a result of this association so that when they marry they are already in non-virgin state. This has an impact on self-confidence for a woman who is about to get married because she is already in a state of virginity, thus triggering the intention to perform hymen surgery. Hymen surgery is focused on intention, if a person does hymen surgery with the intention that her husband does not know that she has had sexual intercourse with other people then this is forbidden, but vice versa if a woman has hymen surgery because of an injury caused not because of Sexual intercourse is permissible under Islamic law.